Organization structure and structural change in European manufacturing organisations - PUGH, Derek (Institutional Knowledge at Singapore Management University, 1996)
The paper considers two approaches to thestudy of the impact of national cultures on thestructure of organizations; viz: culture free andculture bound approaches. Af ter a discussionof the problems of obtaining comparable datain cross-cultural research, the preliminary results of a comparative study of large manufacturing organizations in six countries in Europeare presented. The results suggest that whileformal organizational authority structures appear to be culture free reflecting the impact ofstrategic contingencies, use of coordinationtechniques, such as regular top managementmeetings and task forces, is more affected bycultural factors.